Food consumption trend : transforming issues into opportunities. - Shamsudin, Mad Nasir; Selamat, Jinap; Radam, Alias; Ramin, Abdul Ghariff; Tey, Yeong Sheng; Abdul Hadi, Ahmad Hanis Izani (Federal Agricultural Marketing Authority, 2010)
Economic development has driven the Malaysian food consumption trend to move from basic staple to non-traditional staples – wheat-based, meat, fruit and vegetable items. More affluent Malaysians are also prompted to dine away from home. This paper attempts to acknowledge and grasp the changes in the Malaysian food consumption trend with deliberation for turning relevant issues into opportunities. Income, own price, relative prices, and demographic factors are the driving forces behind the changes in the Malaysian food consumption trend. Of the widening role of income growth, food demand has shifted toward high quality-differentiated characteristics – freshness, safety, texture, and appearance, and consumers are willing to pay for these quality characteristics. The essence of transforming these issues into opportunities is by responding to consumer expectations. An aligned market-led supply chain is proclaimed to offer differentiated and complex food products, which explicitly specifies the value creating activities via information sharing. The Malaysian agri-food supply chain players must also adopt value creation and delivery approach to produce food products that have sufficient value for customers who are willing to pay.